A Field Experiment on the Role of Socioemotional Skills and Gender for Hiring in Turkey - Nas Ozen, Efsan; Hut, Stefan; Levin, Victoria; Munoz Boudet, Ana Maria (World Bank, Washington, DC, 2020)
A vast literature shows the importance of socioemotional skills in earnings and employment, but whether they matter in getting hired remains unanswered. This study seeks to address this question and further investigates whether socioemotional skill signals in job applicants' resumes have the same value for male and female candidates. In a large-scale randomized audit study, an online job portal in Turkey is used to send fictitious resumes to real job openings, collecting a unique data set that enables investigating different stages of candidate screening. The study finds that socioemotional skills appear to be valued only when an employer specifically asks for such skills in the vacancy ad. When not asked for, however, candidates can face a penalty in the form of lower callback rates. A significant penalty is only observed for women, not for men. The study does not find evidence of other gender differences in the hiring process.